2014
DOI: 10.1007/s11250-014-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and per year productivity of sows in four pig farms in the tropics of Mexico

Abstract: The objectives of this study were to estimate the lifetime and per year productivity of sows and to determine the effect of some factor on those traits in four pig farms in the tropics of Mexico. Data from 7526 sows for lifetime number of piglets born alive per sow (LBA), lifetime kilograms of piglets at farrowing (LKF), number of piglets born alive per year (NPF/Y), and kilograms of piglets at farrowing per year (KPF/Y); and data from 7230 sows for lifetime number of piglets weaned (LPW), lifetime kilograms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
2
11
0
9
Order By: Relevance
“…Similarly, Thai researchers found that NBA1 increased as age at first mating increased in Landrace sows [16]. Also in agreement with these results, sums of reproduction traits from the second to the last parity or lifetime production traits were found to decrease as age at first farrowing increased in Landrace (Sweeden; [17]), Yorkshire (Findland; [18]) and in commercial swine herds (Mexico; [19]).…”
Section: Resultssupporting
confidence: 60%
“…Similarly, Thai researchers found that NBA1 increased as age at first mating increased in Landrace sows [16]. Also in agreement with these results, sums of reproduction traits from the second to the last parity or lifetime production traits were found to decrease as age at first farrowing increased in Landrace (Sweeden; [17]), Yorkshire (Findland; [18]) and in commercial swine herds (Mexico; [19]).…”
Section: Resultssupporting
confidence: 60%
“…In Mexico, gilts which had their first farrowing before 337 days of age had higher LBAY, LPWY, LBWY and LWWY than gilts which had their first farrowing after 347 days of age (Ek‐Mex et al . ). Additionally, Saito et al .…”
Section: Resultsmentioning
confidence: 97%
“…Ek‐Mex et al . () reported a LBAY of 23 piglets, 22 piglets for LPWY, 34 kg for LBWY and 125 kg for LWWY in four commercial farms in Mexico. The LPL for Landrace (526 days) and Yorkshire sows (573 days) in this population were lower than in other swine populations in Thailand (806 to 875 days for Landrace and 817 to 884 days for Yorkshire; Keonouchanh ) and Mexico (763 days for Yorkshire; Segura‐Correa et al .…”
Section: Resultsmentioning
confidence: 99%
“…The climate of the region is sub-humid tropical, with average temperature of 26.6°C, average rainfall of 1.100 mm, and relative humidity of 78% (INEGI 2004). The data from the farms used in this study had been previously used in another study about lifetime performance of sows (Ek-Mex et al 2015). Data were obtained from the computer recording system (PigCHAMP ®) of the four farms from 2007 to 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The productivity per year was defined as the number of piglets born alive per sow per year (PBY). PBY was calculated as LBA divided by the total days from entry date and removed or culling date from the breeding herd multiplied by 365 days; when the total days from entry date and removed or culling date was ≤ 365 days, the PBY of a sow was equal to the LBA (Ek-Mex et al 2015). Based on DNBA sows were categorised into eleven groups: ≤ -5,-4, -3, -2, -1, 0, +1, +2, +3, +4 and ≥ +5 piglets.…”
Section: Methodsmentioning
confidence: 99%